Genesis Begins Again - Williams, Alicia 1970- (New York Atheneum Books for Young Readers, 2019)
Thirteen-year-old Genesis tries again and again to lighten her black skin, thinking it is the root of her familys troubles, before discovering reasons to love herself as is.
"A Caitlyn Dlouhy book."
Keywords: Human skin color -- Juvenile fiction; Self-esteem -- Juvenile fiction; Families -- Juvenile fiction; African Americans -- Juvenile fiction; Prejudices -- Juvenile fiction; Moving, Household -- Juvenile fiction